Impact of pegfilgrastim approval on relative dose intensity and outcomes of R-CHOP for diffuse large B-cell lymphoma. Issue 10 (11th March 2022) - Morita, Yuka; Kanemasa, Yusuke; Sasaki, Yuki; Ohigashi, An; Tamura, Taichi; Nakamura, Shohei; Yagi, Yu; Kageyama, Akihiko; Omuro, Yasushi; Shimoyama, Tatsu
Abstract : Abstract: Maintaining relative dose intensity (RDI) of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) improves the prognosis of patients with diffuse large B-cell lymphoma (DLBCL). Pegfilgrastim was approved in Japan in November 2014 to prevent febrile neutropenia (FN) and maintain RDI. In this retrospective study, we reviewed 334 patients with DLBCL who received 6 or more courses of R-CHOP and analyzed the differences in the RDI, overall survival (OS), and progression-free survival between patients whose treatment started after November 2014 (postapproval group) and those whose treatment started before October 2014 (pre-approval group). The incidence of FN was lower (20% vs 38.3%, P < .001) and the RDI of R-CHOP was higher (86.8% vs 67.8%, P < .001) in the postapproval group. Pegfilgrastim was administered to many of these patients (76.8%) and was thought to have contributed to the high RDI maintenance in the postapproval group. Interrupted time-series analysis showed a significant rise of the RDI at the timing of pegfilgrastim approval in patients aged <70 years (estimated change: 18.1%, P < .001). The 5-year OS (85.7% vs 69.9%, P = .009) and progression-free survival (81.4% vs 64.4%, P = .011) were superior in the postapproval group. However, the differences were not significant in matched-pair analysis matching National Comprehensive Cancer Network-International Prognostic Index scores. Improved survival outcomes in this group were observed only among patients with Ann Arbor stage 3/4 (5-year OS: 83.7% vs 61.3%, P = .019) and high-risk on the National Comprehensive Cancer Network-International Prognostic Index (5-year OS: 80.7% vs 32.4%, P = .014). Multivariate analysis showed that a high RDI and low lactate dehydrogenase were associated with superior OS (RDI ≥ 85%, hazard ratio: 0.48, P = .016; lactate dehydrogenase > institutional upper limit of normal, hazard ratio: 2.38, P = .005). The RDI of R-CHOP was able to be maintained at higher levels, the incidence of FN was lower, and significantly better clinical outcomes were achieved in clinically high-risk groups after pegfilgrastim approval. Maintaining a high RDI in R-CHOP by administering pegfilgrastim to those who are likely to have low RDI without it is important for achieving favorable outcomes in patients with DLBCL.